Influence of Assessment Mode Preference on Students’ Test Anxiety, Self-Efficacy, and Academic Performance - Chikezie, Ijeoma Joy; Ehiemere, Francisca Ifeoma; Ayanwale, Musa Adekunle; Okoye, Amaka Charity (PT. Riset Press International, 2026)
The shift toward computer-based testing (CBT) in Nigerian education necessitates a clear understanding of its implications for learners. This study examined the influence of assessment mode preference, computer-based assessment (CBA) versus paper-and-pencil assessment (PPA), on test anxiety, self-efficacy, and academic performance among 312 Senior Secondary School 3 students in the Aba Education Zone, Nigeria. A cross-sectional survey design was employed, with participants randomly drawn from the 2024/2025 SS3 population. Instruments included the Test Anxiety Questionnaire (TAQ), the Computer Self-Efficacy (CSE) Scale, and students’ Mock SSCE GPA. The scales demonstrated strong validity and reliability (S-CVI = 1.00/α = .90; S-CVI = .95/α = .80). Factorial two-way ANOVA tested three hypotheses at the .05 level. Results showed that psychological traits were the strongest predictors of outcomes: test anxiety explained 78% of score variance (η² = .78, p < .05), and self-efficacy explained 82% (η² = .82, p < .001). Assessment mode preference had no significant effect on test anxiety (F = 0.27, p > .05, η² = .001) or self-efficacy (F = 1.80, p > .05, η² = .006). A small but significant effect was observed for academic performance (F = 12.10, p < .05, η² = .038), with CBA-preferring students outperforming their PPA-preferring peers. The findings suggest that while CBA may modestly improve academic performance, successful adoption requires integrating digital literacy training and self-efficacy support to ensure equity and minimize test anxiety.